A pH‐ and Light‐Responsive Nanoporous Lyotropic Gyroid Polymer Network. Issue 5 (4th December 2022) - Li, Patrick; Johnson, Christopher; Dyer, Samantha S.; Osuji, Chinedum O.; Gin, Douglas L.
Abstract: Bicontinuous cubic (Q) lyotropic liquid crystal (LLC)‐derived polymer networks possess periodic, uniform‐size, 3D‐interconnected nanopores that make them highly desirable organic materials for selective molecular separation and uptake applications. To date, there are no reported examples of a Q‐phase network with additional functional properties, such as catalytic reactivity, response to external stimuli, or gated transport, that would expand the usefulness of this class of porous materials. Here, a functionalized gyroid‐type Q polymer network material that can be used for potential gated transport or adaptive uptake applications is presented. This material contains a novel spiropyran‐containing dopant monomer that upon blending and cross‐linking with a gyroid‐forming LLC monomer, yields a gyroid polymer material that retains its phase architecture while reversibly responding to changes in external solution and vapor pH. Studies also demonstrate that this system is capable of strongly binding to aq. Pb 2+ ions when activated by UV light, allowing it to function as a potential colorimetric sorbent or gated‐response material. Abstract : A spiropyran‐based monomer is synthesized and blended with a bicontinuous cubic (Q) phase‐forming lyotropic liquid crystal monomer. Self‐assembly with added water and polymerization yields stimuli‐responsive, gyroid‐type Q‐phase polymer networks. This novel nanoporous gyroid polymer material retains its phase structure while responding to external stimuli such as acid (aqueous solution or vapor phase) or UV light.